TOP TEN MOST PROBLEMATIC GRAMMATICAL ITEMS FOR INDONESIAN TERTIARY EFL LEARNER WRITERS - Rizqi Yusnitasari; Tono Suwartono (Premise: Journal of English Education and Applied Linguistics, 2020)
Errors are almost inseparable from learning process, including learning new languages. Though, it is not always considered as negative, instead, it is a part of learning process. This study was conducted to assess students’ mastery of grammar in writing, to find what grammatical errors they make, to be an evaluation to overcome the problem in the future. In this study, samples were taken from EFL students of English Education Department of Universitas Muhammadiyah Purwokerto. The grammatical errors were identified under the theory of Politzer-Ramirez which classify errors into two types: morphological and syntactic error. In the end of the study, ten types of grammatical errors were identified as the most common grammatical errors made by the students. Three of them belong to morphological error, while the remaining fall into syntactic error. Those ten errors are: The use of prepositions (75 %), redundancy (75 %), simple past tense incorrect (62.5 %), determiners (58.3 %), number confusion (45.8 %), omission of verb (45.8 %), verb construction (41.67 %), derivatives/wrong part of speech (41.67 %), nominalization (33.3 %), and errors in the use of pronoun (29.2 %). Keywords: Problematic, Grammatical Items, Tertiary, EFL, Learner Writers